2012
DOI: 10.2220/biomedres.33.255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microRNA expression in rat lungs caused by sevoflurane anesthesia: a TaqMan^|^reg; low-density array study

Abstract: Reportedly, a large number of microRNAs (miRNAs) play an important role in inflammatory lung diseases such as asthma, idiopathic pulmonary fibrosis (IPF), acute respiratory distress syndrome (ARDS), and pulmonary arterial hypertension (PAH). Sevoflurane is routinely used to various patients, and its safety has been confirmed by clinical outcomes; however, its effects to lungs at the miRNA level have not been elucidated. In our previous genomic studies, we showed that sevoflurane anesthesia affected the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The two drugs have been used extensively in previous studies concerning the effects of anesthetic agents on gene expression (7-9), protein expression (10) and metabolites (11) in the rat brain. Changes in the miRNA expression levels in the hippocampi of rats anesthetized with one minimum alveolar concentration of inhaled anesthetics (sevoflurane at 2.4%; 22) or with continuous infusion of intravenous anesthetics (propofol at 600 µg/kg/min; 23) were investigated in the present study. Infusion of propofol at 600 µg/kg/min is the median effective dose for rats (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two drugs have been used extensively in previous studies concerning the effects of anesthetic agents on gene expression (7-9), protein expression (10) and metabolites (11) in the rat brain. Changes in the miRNA expression levels in the hippocampi of rats anesthetized with one minimum alveolar concentration of inhaled anesthetics (sevoflurane at 2.4%; 22) or with continuous infusion of intravenous anesthetics (propofol at 600 µg/kg/min; 23) were investigated in the present study. Infusion of propofol at 600 µg/kg/min is the median effective dose for rats (26).…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of propofol at 600 µg/kg/min is the median effective dose for rats (26). The two doses were selected since lower doses may not induce adequate anesthesia and higher doses may produce hemodynamic changes (10,22) that may independently alter hippocampal miRNA expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, it was found that sevoflurane affects the expression of miRNAs in normal rat lung (6). However, such effects of anesthetic ALI remain unknown.…”
Section: Introductionmentioning
confidence: 95%
“…On the second day, context testing was conducted 21 h after conditioning in the same chamber. Cued testing with altered context was conducted 26 h after conditioning using a triangular box (28.5 (L) × 32.5 (W) × 32.5 (H) cm) made influence on the expression of miRNAs in major organs such as the liver, lung, and brain of adult rats (5,9,28). Conversely, certain brain-specific miRNA regulates the size of dendritic spines, which are postsynaptic sites of excitatory synaptic transmission of rat hippocampal neurons (24).…”
Section: Contextual and Cued Fear Conditioning Testmentioning
confidence: 99%